Macrozoobenthic invertebrate assemblages in rivers Șușița and Sohodol (Gorj County, Romania) and their indicator value for the water quality characterization - Diana CUPȘA; Antonia CIRLE; Alexandra-Roxana-Maria MAIER; Achim-Mircea CADAR; Ilie Cătălin TELCEAN (Studia Universitatis Babeș-Bolyai. Biologia, 2020)
The present research evaluates the macrozoobenthic invertebrate assemblages from two rivers situated in the Jiu River basin. The invertebrates were collected from three sample sites on Sohodol River and five sample sites on Șușița River. The sample sites were situated along the two rivers which flow almost along their entire length through a forested area. In the case of Sohodol River we have encountered anthropic activities related to seasonal tourism, but no localities or industrial activities were observed in the area. The aim of the study was to establish besides the structure of the macrozoobenthic invertebrate assemblages, the water quality using BMWP score and also to evaluate the human impact on the macrozoobenthos in Sohodol River and the differences between the macrozoobenthic assemblages in the two rivers caused by natural or anthropic factors.